The Effect of Implementation of the Team Games Tournament (TGT) type Cooperative Learning Model on The Learning Outcomes of Islamic Religious Education and Character (PAIBP) for Vocational High School (SMK) Students Al-Hidayah Cirebon - Susi Aprilia Susanti; Muthoharoh Muthoharoh; Suteja Suteja (Jurnal Ilmiah Iqra', 2023)
The Effect of Implementation of the Team Games Tournament (TGT) type Cooperative Learning Model on The Learning Outcomes of Islamic Religious Education and Character (PAIBP) for Vocational High School (SMK) Students Al-Hidayah Cirebon. The Team Games Tournament (TGT)-type cooperative learning model for learning Islamic religious education and character is still rarely implemented at Vocational High School (SMK) Al-Hidayah Cirebon City. The purpose of the study was to determine the effect of the implementation of the Team Games Tournament (TGT) type cooperative learning model on the learning outcomes of Islamic Religious Education and Character (PAIBP) subjects for Al-Hidayah Vocational High School students in Cirebon City. The research method used in this study uses a quantitative approach. Quantitative research in this study is experimental research using a quasi-experimental design. The population in this study were class X students, with a total of 294 students, with a sample of class X TKJ-1 as the experimental class and class X TKR-1 as the control class. Data collection techniques in this study used observation, questionnaires, and tests. The results of this study indicate that the Team Games Tournament (TGT) type cooperative learning model affects the learning outcomes of Islamic Religious Education and Character students at Al-Hidayah Vocational High School (SMK) in Cirebon City. This is based on the significance value obtained of 0.000 0.05 and the t count value of 5.035> t table of 2.028. It can be concluded that Ho is rejected and Ha is accepted. The Teams Games Tournament (TGT) cooperative learning model has an effect of 42.7%, while the remaining 57.3% is influenced by other variables not examined in this study.